Electrospun Fiber-Based Delivery of Carotenoids - Arancibia-Aguilar, C; Riquelme-Hinojosa, N (Elsevier, 2025)
Recently, different technologies have been applied for the encapsulation of carotenoids to improve their chemical stability, bioavailability, antioxidant activity, and antimicrobial performance. In this sense, electrospinning is a helpful tool to obtain functionalized materials, such as nanofibers loaded with carotenoids, due to the great encapsulation efficiency and tailored morphology of the fibril bodies. In addition, electrospinning is considered a green technology since it is a nonthermal process with rapid solvent evaporation. Despite this, different factors can modify the physical properties of fibers, affecting their encapsulation performance. In conclusion, electrospun fibers are promising systems for encapsulating and delivering carotenoids, which can be applied to food products and packaging. © 2025 Elsevier Inc. All rights reserved.